On the constitutive modeling of dual-phase steels at finite strains: a generalized plasticity based approach - Soldatos, Dimitris; Triantafyllou, Savvas P.; Chatzi, Eleni N. (2015)
In this work we propose a general theoretic framework for the derivation of constitutive equations for dual-phase steels, undergoing continuum finite deformation. The proposed framework is based on the generalized plasticity theory and comprises the following three basic characteristics: